2006
DOI: 10.1096/fj.06-6014rev
|View full text |Cite
|
Sign up to set email alerts
|

A brief history of RNAi: the silence of the genes

Abstract: The use of the RNA interference (RNAi) pathway to eliminate gene products has greatly facilitated the understanding of gene function. Behind this remarkable pathway is an intricate network of proteins that ensures the degradation of the target mRNA. In this review, we explore the history of RNAi as well as highlighting recent discoveries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
118
0
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 190 publications
(123 citation statements)
references
References 60 publications
2
118
0
3
Order By: Relevance
“…This is consistent with predictions by others (as reviewed in ref. 41) that the holoRISC is a multiunit complex. In this context it is also noteworthy that native agarose gel-electrophoresis experiments showed that longer (Ͼ100 nt) TBSV ss-and dsRNAs are associated with the high-MW fractions displaying ribonuclease activity (data not shown), indicating that these may be components of the in vivo assembled antiviral holocomplex.…”
Section: Tbsv-preferential Ribonuclease Is Associated With a Discretementioning
confidence: 99%
“…This is consistent with predictions by others (as reviewed in ref. 41) that the holoRISC is a multiunit complex. In this context it is also noteworthy that native agarose gel-electrophoresis experiments showed that longer (Ͼ100 nt) TBSV ss-and dsRNAs are associated with the high-MW fractions displaying ribonuclease activity (data not shown), indicating that these may be components of the in vivo assembled antiviral holocomplex.…”
Section: Tbsv-preferential Ribonuclease Is Associated With a Discretementioning
confidence: 99%
“…The RNAi phenomenon was first reported by Napoli and Jorgensen in 1990 [59]. They found a surprising observation in petunias while trying to deepen the purple color of these flowers.…”
Section: Introductionmentioning
confidence: 89%
“…They introduced a pigment-producing gene under the control of a powerful promoter and observed white color instead of deep purple. Jorgensen named the observed phenomenon "cosuppression", since the expression of both the introduced gene and the homologous endogenous gene was suppressed [53,59]. The suppression of the endogenous gene by the introduction of homologous RNA sequence was first noticed by Romano and Macino in Neurospora crassa in 1992 [58,59].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The establishment of stable silencing was originally thought to be a post-transcriptional process, however, multiple lines of evidence from different organisms suggest that small RNAs also promote silencing in the nucleus at the transcriptional level. It has been shown that small RNAs guide chromatin remodeling proteins to specific DNA sequences by binding to nascent RNA transcripts, leading to cytosine methylation (in plants, fission yeast, and even in mice [8,77]) and deposition of histone modifications (in plants, fission yeast, worms, and flies [78,79]). The interaction between small RNAs and chromatin remodeling factors is reciprocal.…”
Section: Mechanisms That Enable Long-lasting Rnaimentioning
confidence: 99%